Fundamental movement drills for all athletes - Caan, A. F. (The Best of British Track & Field Drills Series, 2009)
High Jump coach and performance enhancement specialist Alex "Fuzz" Caan presents a comprehensive 14-drill functional movement routine designed to assist an athlete in perfecting movement skills. This routine will allow your athlete to develop overall athleticism at an accelerated rate - all while preparing him or her for the rigors of training. Coach Caan begins with an overview of basic anatomy and movement dynamics that focus on the importance of maintaining core stability throughout all movements. He then proceeds with basic movement progression. Unique to this presentation is Caan's utilization of three demonstrators for each drill: One shows proper execution, the second shows improper execution allowing Caan to point out common errors to look for, and the final demonstrator repeats the proper execution. Whether the movement is forward, backwards, sideways or multidirectional, this instruction is certain to help your athletes in any direction while maintaining core control.